The sero-prevalence of brucellosis in cattle and their herders in Bahr el Ghazal region, South Sudan - Madut, Nuol Aywel; Muwonge, Adrian; Nasinyama, George William; Bwalya Muma, John; Godfroid, Jacques; Jubara, Ambrose Samuel; Muleme, James; Kankya, Clovice (PLOS Neglected Tropical Diseases, 2018)
Brucellosis is a worldwide recognized bacterial zoonotic disease. There is currently no information on bovine brucellosis sero-prevalence in South Sudan regardless of the economic, social and public health impact on populations. Therefore, for the first time in 33 years, we report the sero-prevalence of brucellosis in cattle and their herders. Furthermore, we characterize the drivers associated with the disease at the human-animal interface in Bahr el Ghazal region, South Sudan. Methods A total of 893 and 87 animal and human sera respectively were examined between December 2015 and May 2016. Rose Bengal Plate Test (RBPT) and Competitive Enzyme Linked Immuno Sorbent Assay (c-ELISA) were used in parallel to detect anti-Brucella antibodies. Questionnaires were administered to collect relevant metadata used for the association analysis in R version 3.2.3. Odds Ratio (OR) and Confidence Intervals (CI) were determined. Results Overall bovine brucellosis prevalence was 31% (95%CI = 28.0±34.2), with the highest 63% (95%CI = 53±70) and lowest 10% (95%CI = 4.5±20.1) prevalence estimates in Wau and Gogrial states respectively. The bovine sero-prevalence was approximately equally distributed among the male 30.4% (26.9±34.2) and the females 32.5% (26.8±38.7). Poor body condition (OR = 0.22; 95%CI = 0.07±0.54) and larger herd sizes (OR = 0.05; 95%CI = 0.008±0.173) were protective factors for brucellosis, while the opposite was true for the second (OR = 1.70; 95%CI = 1.08±2.67) and third (OR = 2.5; 95%CI = 1.46±4.47) lactation stage. The overall brucellosis sero-prevalence in herders was estimated at 33.3% (23.9± 44.3). Conclusion We report a high prevalence of anti-Brucella antibodies in cattle and their herders in Bahr el Ghazal, indicating an enzootic status in the cattle population being an important source of infection for humans. This represents a genuine public health challenge. Therefore, there is need to raise awareness and build capacity and infrastructure in this fragile state to underwrite future public health strategies for brucellosis.
Keywords: Sero-prevalence; Brucellosis; Cattle; Herders; Bahr el Ghazal region; South Sudan